Structural Controls of the Expansion of Small‐Scale Artisanal Gold of Bouda Area (Kaya‐Goren Green Belt, Burkina Faso) From Remote Sensing - R. A. I. Dao; H. Ilboudo; D. Baratoux (Earth and Space Science, 2024)
Abstract Small‐scale artisanal mining is a vital sector of the economy of Burkina Faso. This activity, correctly regulated, remains essential for the population despite security issues since 2015. Exploration of new areas for gold mining in this condition is difficult but essential to continue extractive activities. It is, therefore, important to define viable corridors, with science‐based evidence for the good prospects, to support artisanal miners’ activities in a way that minimizes the environmental impact. We describe a remote sensing approach to study the structural control of expanding small‐scale artisanal gold activity at the Bouda site and define future mining corridors. This remote sensing approach can also mitigate and remedy environmental impacts. The Minimum Noise Fraction (MNF) is applied to Landsat images (7‐ETM+, 5‐TM, and 8‐OLI, respectively, for 2000, 2011, and 2022) to detect extraction sites and perform a spatiotemporal analysis of the expansion of areas affected by gold extraction. The near‐infrared and mid‐infrared bands of Landsat images significantly contribute to detecting extraction areas. A morphological study of the site over time and Principal Component Analysis (PCA) on Landsat 8‐OLI enable us to perform a lineament analysis. The expansion of mining activity is structurally controlled, as revealed by the correlation between gold occurrences and high lineament densities, especially in the dominant NE‐SW direction. These analyses suggest five potential prospecting corridors in the Bouda site.